On Stabilizing and Accelerating SCF Using ITP in Solving Kohn–Sham Equation (Communications in Computational Physics, 2020)
It is found that imaginary time propagation method can effectively delivera convergent result in solving Kohn–Sham equation, but a sufficient long simulationis needed to reach an accurate enough result, while the self-consistent field iterationmethod for Kohn–Sham equation can be more efficient when it works, but it sometimes suffers from divergence. In this work, we take advantage of the convergence ofimaginary time propagation method by generating a quality initial guess to improvethe behavior of self-consistent field iteration. A number of numerical experiments successfully show that i). for those self-consistent field iterations which are sensitive to theinitial guess, the results obtained from imaginary time propagation method make theiterations converge, and ii). generally, the convergence of self-consistent field iterationcan be accelerated by imaginary time propagation method. It is shown that all-electronmodels can be resolved well with the proposed method.
Keywords: Self-consistent field iteration; imaginary time propagation; finite element method; all-electron calculation.